ANALISIS MESIN FILLING MINYAK GORENG BERBASIS PLC MENGGUNAKAN METODE PENAKAR DAN TIMER UNTUK MENINGKATKAN EFISIENSI - M. Angga Saputra; Ahmad Syuhri; Aris Zainul Muttaqin (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Since 2006 Indonesia has become the world's largest producer of Crude Palm Oil. Also, palm oil is a strategic commodity both as food (cooking oil). The need for self-cooking oil every day is increasing, causing businessmen who plunge not only to have significant capital but many from SMEs and MSMEs who start a cooking industry in the home industry. In the home industry for cooking oil packaging, the manual method is still used, which is to drain oil from the reservoir to the package through a pipe that is given a tap to open and close. This study studied PLC-based cooking oil filling machines using a timer and timer method to improve efficiency, charging speed, errors as small as possible and to increase production capacity. The test results showed that the cooking oil filling process using the measuring method had an average of 159,478 (g / dt) with an average oil yield of 689.2 grams with an error rate of 0.23%. While the timer method has an average filling speed of 164.336 (g / dt) with an average oil yield of 692.08 grams with an error of 0.336%. The timer method has a faster-charging speed compared to the measuring process, but for the error rate, the purpose is better than the timer method. This is due to the way of using the rotary encoder sensor when charging, so the time required for charging is a little long but with a small error rate. While the timer method uses a timer sensor that is on the PLC to make charging directly into the bottle but has a more significant error compared to using the measuring process. For engine capacity, it is better to use a timer method that produces 5145 liters/day while the gauge method is only 4984 liters/day. whereas for efficiency, it is better the process of measuring is 99.68%, and the timer method is 99.27% Keywords: Timer Method, Measuring Method, Cooking Oil Filling Machine and PLC